Genetic aspects of non-motor symptoms in Parkinson’s disease - N. Y. Safonova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Non-motor symptoms are common in Parkinson`s disease and reflect the multisystem nature of the disorder. Parkinson’s disease is highly heterogeneous in early clinical features and later outcomes. This makes classifying genetic subgroups of PD relevant to clinical research and practice, particularly if they are prognostically relevant. Non-motor sypmptoms may be detrimental to patients’ functional status and sense of well-being.